Patient satisfaction with the virtual clinic in Jazan city, Saudi Arabia: A cross-sectional study - Hamzi, Mada Ibrahim; AlSomali, Nasra Hussain; AlSomali, Nadiya Hussain; Mahdi, Mada Mousa; Noshaily, Ali Jubran (International Journal of Innovative Research and Scientific Studies, 2025)
Patient satisfaction is an essential dimension of care quality and an aspect of the spread and adoption of Virtual Clinic facilities. Patient satisfaction assessment has emerged as a critical measure of healthcare performance and outcomes. This study aimed to assess patient satisfaction with a virtual clinic in Jazan City, Saudi Arabia. A cross-sectional study using a convenience sample of 305 patients at a virtual clinic in three general hospitals in the Jazan region of Saudi Arabia was conducted. A quantitative descriptive correlational design was used for the study. The researchers used the Telehealth Satisfaction Scale to measure patient satisfaction with care from the Virtual Clinic. Independent sample t-tests and one-way analysis of variance were used to compare satisfaction scores between groups. The study suggested that patients were very satisfied with their virtual clinic. Overall, the average of most scale items exceeded three, indicating satisfaction ratings between "good" and "excellent." There were no statistically significant associations between sociodemographic characteristics and patient satisfaction with virtual clinics. It is also a relatively new concept in the health sector in the Jazan area, but the high satisfaction of surveyed users motivates further development in that area. For patients, the courtesy, respect, sensitivity, and friendliness of virtual clinic staff, as well as maintaining patients’ privacy, were vital, reporting that virtual clinics could enhance access to care.